A low-voltage programmable-gain current-mode amplifier - De Lima, Jader A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2002)
A CMOS low-voltage, wide-band continuous-time current amplifier is presented. Based on an open-loop topology, the circuit is composed by transresistance and transconductance stages built around triode-operating transistors. In addition to an extended dynamic range, the amplifier gain can be programmed within good accuracy by the rapport between the aspect-ratio of such transistors and tuning biases Vxand Vy. A balanced current-amplifier according to a single I. IV-supply and a 0.35μm fabrication process is designed. Simulated results from PSPiCE and Bsm3v3 models indicate a programmable gain within the range 20-34dB and a minimum break-frequency of IMHz @CL=IpF. For a 200 μApp-level, THD is 0.8% and 0.9% at IKHz and 100KHz, respectively. Input noise is 405pA√Hz @20dB-gain, which gives a SNR of 66dB @1MHz-bandwidth. Maximum quiescent power consumption is 56μ W. © 2002 IEEE.
Keywords: Amplifier gain; Continuous time; Current amplifier; Extended dynamics; Fabrication process; Gain current; Input noise; Low-voltage; Open loops; Power Consumption; Programmable gain; Simulated results; Transconductance stage; Transresistance; Wide-band; Aspect ratio; Computer simulation; Broadband amplifiers